Collectivism-oriented human resource management on team creativity: effects of interpersonal harmony and human resource management strength. Issue 18 (11th October 2021) - Chen, Silu; Fan, Youqing; Zhang, Guanglei; Zhang, Yu
Abstract: This study examines the mechanism through which collectivism-oriented human resource management (CHRM) promotes team creativity and how this relationship differs across interpersonal harmony. Drawing on social exchange theory, we investigate 177 research and development teams across China. The findings indicate, as expected, that CHRM, which in China relates to guanxi, has a positive effect on radical creativity. Harmony enhancement partially mediates the relationship between CHRM and radical creativity. Meanwhile, disintegration avoidance fully mediates the relationship between CHRM and incremental creativity. In addition, HRM strength positively moderates the relationship between CHRM and harmony enhancement. Finally, HRM strength moderates the mediating effect between CHRM and radical creativity. This study helps unpack the 'black box' between culture-specific HRM and team outcomes, providing important implications for human resource managers.